Topical Microneedle Drug Delivery Enhanced with Magnetophoresis - Prow, T.; Mohammed, Y.; Ansaldo, A.; Benson, Heather (The Royal Society of Chemistry, 2014)
Proteins and peptides are coming of age as targeted biological therapies. A broad range of peptides have now been approved by the FDA and other regulatory agencies for use as therapeutics. Likewise, large proteins such as infliximab and botox are commonly used to treat skin conditions. The most widely used delivery approach for peptides and proteins is parenteral injection, largely due to oral instability and the lack of a suitable alternative. Intense research is being done to improve the short half-lives of these biological therapies and find suitable alternative delivery routes. Transdermal delivery holds promise as an improved delivery route because the skin has low levels of enzymatic activity and can help drugs avoid first-pass metabolism. Further, topical delivery has the potential for direct treatment of skin disease for both therapeutic and cosmetic applications.